Endoscopic Diagnosis of Leiomyosarcoma of the Esophagus, a Rare Neoplasm - Ravini, Mario (Hindawi Publishing Corporation, 1998)
We report a case of leiomyosarcoma of the distal third of the esophagus in a 51-year-old woman presenting with a six-month history of severe epigastric pain, disphagia and weight loss. The diagnosis, suspected on endoscopic examination, was preoperatively acheived by biopsy and immunohistological stain. Surgical treatment was undertaken with good results. Differentiation between leiomyosarcoma and more common esophageal neoplasm may be difficult if based on radiographic and endoscopic appearance. Preoperative histological confirmation is therefore mandatory to schedule a wide surgical excision.